Proximal contact tightness between direct-composite additions in the posterior dentition: an in vitro investigation - Wolff, Diana; Hahn, Philipp; Ding, Paul Georg Friedrich; Maier-Kraus, Theresa; Frese, Cornelia; Staehle, Hans Jörg (Operative dentistry, 2012)
Clinical Relevance A novel three-step matrix technique for the application of posterior direct-composite additions was tested in vitro. It was proven that by using this technique the reconstruction of proximal contacts and the creation of well-contoured proximal surfaces between direct-composite additions are feasible in an in vitro setting. The preclinical testing of this novel technique is necessary to establish the work flow for clinical application and to acquire data for planning in vivo investigations.